Motivational Interviewing as Governmentality: Shaping Victims of Men's Violence into Responsible Subjects? - Lauri, Marcus (NORA : Nordic journal of women's studies, 2019)
Motivational interviewing (MI) is an evidence-based counselling method that has spread rapidly in Sweden during the last two decades. It is a technique designed to empower individuals to change an unwanted life situation. Through interviews with a strategic sample of persons engaged in work with men's violence against women, this article critically examines the use of MI in this context. By analysing the interviews from a governmentality perspective, it is suggested that MI is a technique to produce a knowledgeable, strong, and self-animated feminine subject, capable of making the "right" choices and subsequently "choosing" to avoid violence. Although this may be beneficial to some, the analysis suggests that this places primary responsibility on the woman subjected to violence for her predicament and future. This may in turn increase the risk of self-blame for those who cannot follow through with their commitment, and obscure and renounce the role and responsibility of both the counsellor and the rationalized neoliberal welfare state. In addition, the one-sided focus on the individual largely ignores the surrounding context, which may obscure men's responsibility for violence. This may ultimately undermine the collective formation of a political subject from women's shared experience of violence.